Theatre : An exhibition of 20th century theatrical designs and drawings - Spencer, Charles; Galerie Liatowitsch, Basel; Galerie Bargera, Köln; Galleria Milano, Milano (London : Annely Juda Fine Art London, 1974)
Alastair ; Andreenko, Michel ; Anisfeld, Boris ; Annals, Michael ; Armfield, Maxwell ; Bakst, Leon ; Barbier, George ; Beaton, Cecil ; Benois, Alexandra ; Berard, Christian ; Berman, Eugene ; Bianchini, Charles ; Bilinsky, Boris ; Blatas, Arbit ; Blond, Maurice ; Bomberg, David ; Chompre, S. ; Cocteau, Jean ; Colin, Paul ; Craig, Edward Gordon ; Derain, André ; Erte ; Exter, Alexandra ; de Feure, Georges ; Fini, Leonor ; Fraser, Claud Lovat ; Gamlin, R. ; Georgiadis, Nicholas ; Gesmar, Charles ; Gontcharova, Natalia ; Gross, Valentine ; Haffenden, Elisabeth ; Halouze, Edouard ; Hokerman, Alice ; Irving, Laurence ; Kay, Barry ; Korovine, Constantin ; Krivoutz, Vladimir ; Laforge, Lucien ; Larionov, Michail ; Laurencin, Marie ; Laurent, Yves Saint ; Lewis, Wyndham ; Lissim, Simon ; Manuel, J.F.L. ; Mohanti, Profulla ; Nobili, Lila da ; Orr, Chris ; Pevsner, Antoine ; de Pogedaiff, Georges ; Poiret, Paul ; Price, D.C.S. ; Procktor, Patrick ; Ranson, René ; Remisoff, Nicolai ; Richie, Augustus P.F. ; Ricketts, Charles ; Sainthill, Loudon ; Seltenhammer, Paul ; Sonnabend, Yolande ; Soudeikine, Serge ; Sperling, Ian ; Stern, Ernest ; Stevenson, Hugh ; Svoboda, Josef ; Tree, Dolly ; Wevern ; Willoughby, Hugh ; Wittop, Freddy ; de Zamora, José ; Zig ; Zinoviev
biog. per kunstenaar
Engels & Duits & Italiaans
Theatre : An exhibition of 20th century theatrical designs and drawings, Annely Juda Fine Art, London, 2 October - 2 November 1974 ; Galerie Bargera, Köln, November - December 1974 ; Galerie Liatowitsch, Basel, January - February 1975 ; Galleria Milano, Milano, March - April 1975
boek